Single-cell time series analysis reveals the dynamics of HSPC response to inflammation - Bouman, Brigitte J.; Demerdash, Yasmin; Sood, Shubhankar; Grünschläger, Florian; Pilz, Franziska; Itani, Abdul Rahman; Kuck, Andrea; Marot-Lassauzaie, Valérie; Haas, Simon; Haghverdi, Laleh; Essers, Marieke (Life science alliance, 2024)
Hematopoietic stem and progenitor cells (HSPCs) are known to respond to acute inflammation; however, little is understood about the dynamics and heterogeneity of these stress responses in HSPCs. Here, we performed single-cell sequencing during the sensing, response, and recovery phases of the inflammatory response of HSPCs to treatment (a total of 10,046 cells from four time points spanning the first 72 h of response) with the proinflammatory cytokine IFN alpha to investigate the HSPCs' dynamic changes during acute inflammation. We developed the essential novel computational approaches to process and analyze the resulting single-cell time series dataset. This includes an unbiased cell type annotation and abundance analysis post inflammation, tools for identification of global and cell type-specific responding genes, and a semi-supervised linear regression approach for response pseudotime reconstruction. We discovered a variety of different gene responses of the HSPCs to the treatment. Interestingly, we were able to associate a global reduced myeloid differentiation program and a locally enhanced pyroptosis activity with reduced myeloid progenitor and differentiated cells after IFN alpha treatment. Altogether, the single-cell time series analyses have allowed us to unbiasedly study the heterogeneous and dynamic impact of IFN alpha on the HSPCs.